Molecular cloning and characterization of a brassinosteriod biosynthesis-related gene PtoDWF4 from Populus tomentosa. (22nd March 2018) - Shen, Yun; Li, Yongli; Xu, Dan; Yang, Chen; Li, Chaofeng; Luo, Keming
Abstract: Brassinosteroids (BRs) as steroid hormones play an important role in plant growth and development. However, little is known about how BRs affect secondary wall biosynthesis in woody plants. In this study, we cloned and characterized PtoDWF4, a homologus gene of Arabidopsis DWF4 encoding a cytochrome P450 protein, from Populus tomentosa . qRT-PCR analysis showed that PtoDWF4 was highly expressed in stems, especially in xylem. Overexpression of PtoDWF4 ( PtoDWF4-OE ) in poplar promoted growth rate and biomass yield, increased area and cell layers of xylem. Transgenic plants showed a significant increase in plant height and stem diameter compared with the wild type. In contrast, the CRISPR/Cas9-generated mutation of PtoDWF4 ( PtoDWF4-KO ) resulted in significantly decreased biomass production in transgenic plants. Further studies revealed that constitutive expression of PtoDWF4 up-regulated the expression of secondary cell wall (SCW) biosynthesis-related genes, whereas knock-out of PtoDWF4 down-regulated their expression. Quantitative analysis of cell wall components showed a significant increase in PtoDWF4-OE lines but a reduction in PtoDWF4-KO lines compared with wild-type plants. Taken together, our results indicate that PtoDWF4 plays a positive role in improving growth rate and elevating biomass production in poplar.